Analysis of agonist and antagonist effects on thyroid hormone receptor conformation by hydrogen/deuterium exchange - Figueira, A. C M; Saidemberg, D. M. [UNESP]; Souza, P. C T; Martínez, L.; Scanlan, T. S.; Baxter, J. D.; Skaf, M. S.; Palma, Mario Sergio [UNESP]; Webb, P.; Polikarpov, I. (The Endocrine Society, 2011)
Thyroid hormone receptors (TRs) are ligand-gated transcription factors with critical roles in development and metabolism. Although x-ray structures of TR ligand-binding domains (LBDs) with agonists are available, comparable structures without ligand (apo-TR) or with antagonists are not. It remains important to understand apo-LBD conformation and the way that it rearranges with ligands to develop better TR pharmaceuticals. In this study, we conducted hydrogen/deuterium exchange on TR LBDs with or without agonist (T 3) or antagonist (NH3). Both ligands reduce deuterium incorporation into LBD amide hydrogens, implying tighter overall folding of the domain. As predicted, mass spectroscopic analysis of individual proteolytic peptides after hydrogen/ deuterium exchange reveals that ligand increases the degree of solvent protection of regions close to the buried ligand-binding pocket. However, there is also extensive ligand protection of other regions, including the dimer surface at H10-H11, providing evidence for allosteric communication between the ligand-binding pocket and distant interaction surfaces. Surprisingly, Cterminal activation helix H12, which is known to alter position with ligand, remains relatively protected from solvent in all conditions suggesting that it is packed against the LBD irrespective of the presence or type of ligand. T 3, but not NH3, increases accessibility of the upper part of H3-H5 to solvent, and we propose that TR H12 interacts with this region in apo-TR and that this interaction is blocked by T 3 but not NH3.Wepresent data from site-directed mutagenesis experiments and molecular dynamics simulations that lend support to this structural model of apo-TR and its ligand-dependent conformational changes. (Molecular Endocrinology 25: 15-31, 2011). Copyright © 2011 by The Endocrine Society.
Keywords: amide; ammonia; binding protein; deuterium; dimer; hormone receptor affecting agent; hormone receptor blocking agent; hydrogen; ligand; ligand binding protein; peptide; solvent; thyroid hormone receptor; thyroid hormone receptor agonist; thyroid hormone receptor antagonist; unclassified drug; allosterism; carboxy terminal sequence; controlled study; deuterium hydrogen exchange; dimerization; female; human; human cell; ligand binding; mass spectrometry; priority journal; protein conformation; protein degradation; protein domain; protein expression; protein function; protein protein interaction; surface property; Amino Acid Sequence; Ammonia; Apoproteins; Deuterium; Deuterium Exchange Measurement; Humans; Ligands; Molecular Dynamics Simulation; Molecular Sequence Data; Mutation; Peptides; Protein Structure, Secondary; Protein Structure, Tertiary; Receptors, Thyroid Hormone; Sequence Alignment; Solvents; Triiodothyronine